Copyright Protection for Songs Uploaded to the Spotify Digital Music Application Without Permission - Maichel Lesnussa; Theresia Nolda Agnes Narwadan; Muchtar Anshary Hamid Labetubun (Batulis Civil Law Review)
Introduction: Copyright holders can and have the right to determine who can use their work or not.However,Uploading songs by Spotify application users can unknowingly trigger copyright infringement.